Scientific Opinion on the safety and efficacy of Kemzyme® Plus Liquid (endo‐1,3(4)‐beta‐glucanase, endo‐1,4‐beta‐glucanase, alpha‐amylase and endo‐1,4‐beta‐xylanase) as a feed additive for poultry species and ornamental birds - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (EFSA Journal, 2015)
Abstract The additive Kemzyme® Plus Liquid is an enzyme preparation with four glycosyl hydrolases to be used in poultry species and ornamental birds. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) considered that the additive is safe at the maximum dose of 200 mg additive/kg feed in chickens for fattening and laying hens and at a maximum dose of 150 mg additive/kg feed in turkeys for fattening. The conclusions can be extended to chickens reared for laying and turkeys reared for breeding at the corresponding dose. Similarly, the conclusions can be extrapolated to minor poultry species for fattening and laying and ornamental birds at 200 mg additive/kg feed. The Panel considers that the use of Kemzyme® Plus Liquid as a feed additive gives rise to no concerns for consumers. Kemzyme® Plus Liquid is not an irritant to skin and eyes but should be considered as a potential skin sensitiser. The additive is considered to be hazardous by inhalation. No risks to the environment are expected and no further environmental risk assessment is required. Owing to the incompleteness of the data on enzyme recovery, the FEEDAP Panel could not establish the efficacious dose in units of enzyme activity. The efficacy studies showed that supplementation of the diets with Kemzyme® Plus Liquid at a nominal dose of 50 mg additive/kg feed has the potential to be efficacious in chickens and turkeys for fattening and in laying hens. These conclusions can be extended at the same nominal dose to chickens reared for laying and turkeys reared for breeding and extrapolated to minor poultry species and ornamental birds.